2004
DOI: 10.1097/01.ju.0000125241.77517.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum and Seminal Levels of Prostate Specific Antigen in Men With Spinal Cord Injury

Abstract: SCI patients have a significant decrease in total seminal PSA but total serum PSA is not affected by this lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…This finding suggests that some neurogenically mediated factor plays a role in the PSA production and that this spinal cord level (T7) represents a crucial point in the neurogenic stimulation of the prostate gland. Lynne et al 18 and Alexandrino et al 20 also found that seminal PSA concentrations obtained from patients were lower than those obtained from controls. However, in the study of Alexandrino et al, 20 total seminal PSA was lower in patients compared to controls regardless of lesion level with no difference between levels at T7 and below T7.…”
Section: Seminal Plasma Prostate-specific Antigen Levels In Men With mentioning
confidence: 95%
See 4 more Smart Citations
“…This finding suggests that some neurogenically mediated factor plays a role in the PSA production and that this spinal cord level (T7) represents a crucial point in the neurogenic stimulation of the prostate gland. Lynne et al 18 and Alexandrino et al 20 also found that seminal PSA concentrations obtained from patients were lower than those obtained from controls. However, in the study of Alexandrino et al, 20 total seminal PSA was lower in patients compared to controls regardless of lesion level with no difference between levels at T7 and below T7.…”
Section: Seminal Plasma Prostate-specific Antigen Levels In Men With mentioning
confidence: 95%
“…Lynne et al 18 and Alexandrino et al 20 also found that seminal PSA concentrations obtained from patients were lower than those obtained from controls. However, in the study of Alexandrino et al, 20 total seminal PSA was lower in patients compared to controls regardless of lesion level with no difference between levels at T7 and below T7. The results are shown in Table 3.…”
Section: Seminal Plasma Prostate-specific Antigen Levels In Men With mentioning
confidence: 95%
See 3 more Smart Citations